The Impacts of Genistein and Daidzein on Estrogen Conjugations in Human Breast Cancer Cells: A Targeted Metabolomics Approach - Poschner, Stefan; Maier-Salamon, Alexandra; Zehl, Martin; Wackerlig, Judith; Dobusch, Daniel; Pachmann, Bettina; Sterlini, Konstantin L.; Jäger, Walter (Frontiers in Pharmacology, 2017)
The beneficial effect of dietary soy food intake, especially for women diagnosed with breast cancer, is controversial, as in vitro data has shown that the soy isoflavones genistein and daidzein may even stimulate the proliferation of estrogen-receptor alpha positive (ERα+) breast cancer cells at low concentrations. As genistein and daidzein are known to inhibit key enzymes in the steroid metabolism pathway, and thus may influence levels of active estrogens, we investigated the impacts of genistein and daidzein on the formation of estrogen metabolites, namely 17β-estradiol (E2), 17β-estradiol-3-(β-D-glucuronide) (E2-G), 17β-estradiol-3-sulfate (E2-S) and estrone-3-sulfate (E1-S) in estrogen-dependent ERα+ MCF-7 cells. We found that both isoflavones were potent inhibitors of E1 and E2 sulfation (85-95% inhibition at 10 µM), but impeded E2 glucuronidation to a lesser extent (55-60% inhibition at 10 µM). The stronger inhibition of E1 and E2 sulfation compared with E2 glucuronidation was more evident for genistein, as indicated by significantly lower inhibition constants for genistein [Kis: E2-S (0.32 µM) < E1-S (0.76 µM) < E2-G (6.01 µM)] when compared with those for daidzein [Kis: E2-S (0.48 µM) < E1-S (1.64 µM) < E2-G (7.31 µM)]. Concomitant with the suppression of E1 and E2 conjugation, we observed a minor but statistically significant increase in E2 concentration of approximately 20%. As the content of genistein and daidzein in soy food is relatively low, an increased risk of breast cancer development and progression in women may only be observed following consumption of high-dose isoflavone supplements. Further long-term human studies monitoring free estrogens and their conjugates are therefore highly warranted to evaluate the potential side effects of high-dose genistein and daidzein, especially in patients diagnosed with ERα+ breast cancer.